2013
DOI: 10.1177/0143034312472758
|View full text |Cite
|
Sign up to set email alerts
|

Adversity and resilience: A synthesis of international research

Abstract: Children and adolescents worldwide experience a variety of adversities that have the potential to disrupt typical development. However, some of these individuals exhibit resilience, evidencing normal development in the face of adversity. Here we review research on these constructs of risk, adversity, and resilience; synthesize international research on factors that may serve to protect children and adolescents from the negative effects of adversity at the individual, family, school, community, and cultural lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 61 publications
1
66
0
11
Order By: Relevance
“…Therefore, as suggested by Hong and Espelage (2012), the microsystem level analysis of school bullying behavior needs to consider peer relationship or peer support. Previous studies indicated that peer support could function as a protective factor to promote psychological well-being of school students under adverse conditions (Noltemeyer & Bush, 2013). For example, in the developmental transition from early to middle adolescence, the peer support could be a protective factor diminishing the magnitude of depressive symptoms among white youth (Vaughan, Foshee, & Ennett, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, as suggested by Hong and Espelage (2012), the microsystem level analysis of school bullying behavior needs to consider peer relationship or peer support. Previous studies indicated that peer support could function as a protective factor to promote psychological well-being of school students under adverse conditions (Noltemeyer & Bush, 2013). For example, in the developmental transition from early to middle adolescence, the peer support could be a protective factor diminishing the magnitude of depressive symptoms among white youth (Vaughan, Foshee, & Ennett, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Like most developing countries Liberia's response to Ebola was greatly hampered by the lack of formal instrument for predicting chemical hazard, natural disasters and deadly diseases-an essential part of any basic healthcare infrastructure that would provide a potentially endless as well as essential resources for societal characteristics that can promote or inhibit resilience [21]. The following comments from interviewees confirm the recommendations in the advisory group's report for WHO reform [30].…”
Section: Discussionmentioning
confidence: 77%
“…Proceedings of the 50th Hawaii International Conference on System Sciences | 2017 URI: http://hdl.handle.net/10125/41460 ISBN: 978-0-9981331-0-2 CC-BY-NC-ND structure would bend, but would be hard to break [21].…”
mentioning
confidence: 99%
“…The results of this study suggest that the promotion of conditions related to positive development, such as social skills, self-efficacy and the perception of social support, may indicate a path for the development of well-being and quality of life of adolescents in an unfavorable economic situation (Amparo et al, 2008;Marques & Dell'Aglio, 2013;Juliano & Yunes, 2014;Noltemeyer & Bush, 2013;Zolkoski & Bullok, 2012). The promotion of these skills can also generate resilience processes, as they operate in the empowerment of adolescents, enabling them to deal with adverse situations that require social skills, for example, required in relationships with family members, peers, teachers and romantic partners and in the work context.…”
Section: Discussionmentioning
confidence: 80%
“…In this sense, some studies (Amparo, Galvão, Cardenas, & Koller, 2008;Marques & Dell'Aglio, 2013;Juliano & Yunes, 2014;Noltemeyer & Bush, 2013;Zolkoski & Bullok, 2012) have shown that the social skills, self-efficacy and the perception of social support are, in the case of adolescents, internal and external resources which work interdependently to prevent or mitigate the negative effects of some psychosocial risks. Moreover, researchers that align to the Positive Youth Development approach (Benson et al, 2006;Catalano et al, 2002), highlight the importance of these personal skills and resources of the context for adolescents to optimize their potential at facing possible negative life circumstances, thus acting in the promotion of health and wellness.…”
Section: Social Skills Self-efficacy Beliefs and The Perception Of Smentioning
confidence: 99%